Complex Event Processing in e-Services - Fleischmann, Alber; Schmidt, Werner; Stary, Christian (Proceedings (International Conference on Developments in eSystems Engineering. Print), 2016)
On one hand, today's communities, such as smart regions, undergo continuous development and change. E-services, in particular those relating to ICT-operated infrastructures, form the backbone of those communities. They need to be highly responsive, and react in a context-sensitive and informed way to events occurring in the environment. On the other hand, ICT-based services increasingly propagate in a concentrated way to a variety of infrastructures and become inherent parts of societal systems. Thereby, the complexity of the corresponding ICT architecture steadily increases. This trend conflicts with the flexible adaptation of ICT and the controllability of processes and underlying service architectures by humans. It requires rethinking the way ICT-based services are organized. In this contribution, we describe how event-based systems can become integral part of an actor-driven architecture based on subject-oriented representations. The approach is grounded on communication patterns between acting entities (artefacts or humans), allowing to implement service infrastructures in a federated while adaptable way. Due to the capability to execute models without further transformation, each representation can be validated before being put to operation, and software agents can be assigned in a flexible way. Due to the straightforward modeling scheme, stakeholders can be qualified to control and (re-)design complex service infrastructures.